Creating a 3D village model with multi-source data model integration: application for the protection of ethnic architectural heritage - Cai Jun; Qu Jin-liang; Wang Hai-bo (Conservation Science in Cultural Heritage)
Ethnic architectural heritage is mainly concentrated in ancient villages. The 3D models of ancient villages are of great significance in the protection of the ethnic architectural heritage in ancient villages. The aim of this study is to integrate multi-source data models to form a 3D model of ancient villages, which can provide detailed records of the ethnic architectural heritage and the surrounding environment and ensure that the memory space of the model is as small as possible. This will provide data support for the construction planning and physical protection of ethnic architectural heritage in ancient villages. Taking Hexi Village in He-jie Town of Guang-xi as a case study, different types of architectural models of ancient villages were modeled using technologies such as oblique photogrammetry, point cloud data, and BIM modeling. Through the fusion of multiple data models, a 3D model of the ancient village was successfully constructed, providing an important digital foundation for the protection and restoration of ethnic architectural heritage, opening up new ideas for the digital protection of traditional villages, and laying the foundation for subsequent research on digital twins of ethnic architectural heritage in ancient villages.